Análise energética e exergética de sistemas de cogeração em usinas de cana-de-açúcar - Francischetti, Felipe Rigone [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The sugarcane is a widely cultivated product in São Paulo state and is used in the production of sugar and ethanol. The byproduct of this production, the bagasse, is used as a fuel in the boilers of systems of cogeneration from sugarcane mills, allowing the generation of electric energy together with the thermic exploitation of the steam generated in those systems, which is used in the plant and, in case of surplus, can be sold for the concessionaire of energy supply. The energy analysis allows the quantification of the production, the consume and eventually sale of the electric energy. However, it is not a complete analysis tool, being necessary the complimentary use of the exergy analysis. Using the exergy, this analysis identifies the irreversibilities present in the systems, allowing basement for the optimization of each equipment in use, in order to increase the individual efficiency and, in consequence, the cycle global efficiency. In this work is realized a comparison between two systems based in plants of real sugarcane industries. The first system, denominated case 1, represents a basic configuration and in the second, denominated case 2, there are proposed technological innovations. There are made energy and exergy analysis to evaluate the power generation and consumption, the irreversibilities and the efficiencies of the equipment and the systems used. An algorithm was elaborated to facilitate the calculation. The results show that the system of case 2 is superior than the one in case 1 in all the evaluated parameters, presenting improvement of 10.73 % in energy efficiency and 7.81 % in exergy efficiency. Thus, it was possible to validate the improvement made as options to be followed for real industries that look for increase the efficiency of their systems

cana-de-açúcar é um produto largamente cultivado no estado de São Paulo e é usada para a produção de açúcar e etanol. O subproduto dessa produção, o bagaço de cana, é usado como combustível em caldeiras dos sistemas de cogeração das usinas sucroalcooleiras, que permitem a geração de energia elétrica junto ao aproveitamento térmico do vapor gerado nesses sistemas, que é usada na planta e, em caso de excedente, pode ser vendida para a concessionária de abastecimento de energia. A análise energética permite a quantificação da produção, do consumo e da eventual venda de energia elétrica. Entretanto, não é uma ferramenta de análise completa, sendo necessário o uso complementar da análise exergética. Fazendo o uso da exergia, essa análise identifica as irreversibilidades presentes nos sistemas, o que permite o embasamento para a otimização de cada equipamento usado, de modo a aumentar sua eficiência individual e, em consequência, a eficiência global do ciclo. Neste trabalho é realizada uma comparação entre dois sistemas baseados em plantas de usinas sucroalcooleiras reais. O primeiro sistema, denominado caso 1, representa uma configuração básica e no segundo, denominado caso 2, são propostas inovações tecnológicas. São feitas análises energética e exergética para avaliar as potências geradas e consumidas, as irreversibilidades e as eficiências dos equipamentos e dos sistemas de cada caso. Um algoritmo foi elaborado para facilitar os cálculos. Os resultados mostram que o sistema do caso 2 é superior ao do caso 1 em todos os parâmetros avaliados, apresentando melhoria de 10,73 % na eficiência energética e de 7,81 % na eficiência exergética. Assim, foi possível validar as melhorias feitas como opções a serem seguidas por usinas reais que buscam aumentar a eficiência de seus sistemas
Energy and exergetic analysis of cogeneration systems in sugarcane plants
Keywords: Energia eletrica e calor - Cogeração; Energia - Fontes alternativas; Biomassa; Renewable energy sources